Intergenerational Risk-Sharing through Funded Pensions and Public Debt - Damiaan H.J. Chen; Roel Beetsma; Eduard Ponds; Ward E. Romp (Center for Economic Studies and ifo Institute (CESifo), 2014)
We explore the benefits of intergenerational risk-sharing through both private funded pensions and via the public debt. We use a multi-period overlapping generations model with a PAYG pension pillar, a funded pension pillar and a government. Shocks are smoothed via the public debt and variations in the indexation of pension entitlements and the pension contribution rate, which both respond to funding ratio of the pension fund. The intensity of these adjustments increases when the funding ratio or the public debt ratio get closer to their boundaries. The best-performing pension arrangement is a hybrid funded scheme in which both contributions and entitlement indexation are deployed as stabilisation instruments. We find trade-offs between the optimal use of these instruments. We also find that entitlement indexation and the response of the tax rate to public debt movements are complements. We compare different taxation regimes and conclude that a regime in which pension benefits are taxed, while contributions are paid before taxes, is preferred to a regime in which contributions are paid after taxes, while benefits are untaxed.
Keywords: G23; H55; H63; 330; intergenerational risk-sharing; pension funds; public debt; EET and TEE tax regimes; welfare